Adsorptive Desulfurization of Iraqi Heavy Naphtha Using Different Metals over Nano Y Zeolite on Carbon Nanotube - Mousa, Hussam Jumaah; Hussein, Hussein Qasim (Iraqi Journal of Chemical and Petroleum Engineering, 2020)
The present research was conducted to reduce the sulfur content of Iraqi heavy naphtha by adsorption using different metals oxides over Y-Zeolite. The Y-Zeolite was synthesized by a sol-gel technique. The average size of zeolite was 92.39 nm, surface area 558 m2/g, and pore volume 0.231 cm3/g. The metals of nickel, zinc, and copper were dispersed by an impregnation method to prepare Ni/HY, Zn/HY, Cu/HY, and Ni + Zn /HY catalysts for desulfurization. The adsorptive desulfurization was carried out in a batch mode at different operating conditions such as mixing time (10,15,30,60, and 600 min) and catalyst dosage (0.2,0.4,0.6,0.8,1, and 1.2 g). The most of the sulfur compounds were removed at 10 min for all catalyst types. The maximum sulfur removal was 56% using (Ni+Zn)/HY catalyst at 1.2 g dose for 24 h. The adsorption kinetics and isotherm of sulfur removal were studied, and results indicated that desulfurization adsorption kinetic was 2nd order, and Temkin and Freundlich models were the best representation isotherm.